A. \(P = 6\).
B. \(P = 2\sqrt 2 + 3\).
C. \(P = 2 + 3\sqrt 2 \).
D. \(P = \sqrt {17} + \sqrt 3 \).
B
Từ \(\ln x + \ln y \ge \ln \left( {{x^2} + y} \right) \Leftrightarrow xy \ge {x^2} + y\). Ta xét:
Nếu \(0 < x \le 1\) thì \(y \ge xy \ge {x^2} + y \Leftrightarrow 0 \ge {x^2}\) mâu thuẫn.
Nếu \(x > 1\) thì \(xy \ge {x^2} + y \Leftrightarrow y\left( {x - 1} \right) \ge {x^2} \Leftrightarrow y \ge \frac{{{x^2}}}{{x - 1}}\). Vậy \(P = x + y \ge x + \frac{{{x^2}}}{{x - 1}}\).
Ta có \(f\left( x \right) = x + \frac{{{x^2}}}{{x - 1}}\) xét trên \(\left( {1; + \infty } \right)\).
Có \(f'\left( x \right) = \frac{{2{x^2} - 4x + 1}}{{{x^2} - 2x + 1}} = 0 \Leftrightarrow \left[ \begin{array}{l}x = \frac{{2 - \sqrt 2 }}{2}(loai)\\x = \frac{{2 + \sqrt 2 }}{2}(nhan)\end{array} \right.\)
Vậy \(\mathop {\min }\limits_{\left( {1; + \infty } \right)} f\left( x \right) = f\left( {\frac{{2 + \sqrt 2 }}{2}} \right) = 2\sqrt 2 + 3\).
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247